Accessibility of condoms to young people in Manchester, UK. Issue 4 (1st October 2006) - Sixsmith, Judith; Griffiths, John; Hughes, John; Wren, Joanne; Penfold, Steve; Natusch, Hilary
Abstract : Background and methodology: Issues relevant to the accessibility of male condoms for young people in the Greater Manchester area (UK) were investigated, using semi-structured, in-depth interviews and a questionnaire survey. Results: Family planning clinics and condom vending machines (CVMs) were the most cited sources for condom acquisition. Young people's knowledge of where and when they could access condoms varied by age and gender. Suitable positioning of CVMs would need to take such variations into account when targeting potential customers. Levels of embarrassment about acquiring condoms also varied according to gender. The lifestyles of young people indicated the sorts of places in which CVMs might offer increased accessibility. For younger men and women this tended to involve low-cost, semi-private places such as local parks, school toilets and shopping malls/streets. Older men with higher spending power and increased confidence could access condoms through pub and club toilets and chemist shops. Conclusions: Accessible positioning of CVMs was related to the age, gender and lifestyle of the participants, and programmes to enhance accessibility should reflect this. Increased accessibility for younger groups, and especially women, needs to take into account issues of cost, confidence and embarrassment. For older groups, lifestyle choices indicated pubs and clubs as key locations for both men and women.